Tourism Perspectives and Practices - Sabah, Şenay (IntechOpen, 2019)
Tourism is an important phenomenon of today's global world and is regarded as the world's biggest industry. As a concept, tourism inspires attention from different scientific areas and can be considered within an interdisciplinary context. Due to its multidisciplinary, multidimensional, and multimethod character, tourism is an area ripe for study. This book is a modest try for that end. The chapters are written from economic, managerial, marketing, and educational perspectives, using different frameworks and methodologies.